Genome-Wide DNA Methylation Enhances Stemness in the Mechanical Selection of Tumor-Repopulating Cells - Huang, Wei; Hu, Hui; Zhang, Qiong; Wang, Ning; Yang, Xiangliang; Guo, An-Yuan (Frontiers in Bioengineering and Biotechnology, 2020)
Background: DNA methylation plays essential roles in tumor occurrence and stemness maintenance. Tumor-repopulating cells (TRCs) are cancer stem cell (CSC)-like cells with highly tumorigenic and self-renewing abilities, which were selected from tumor cells in soft three-dimensional (3D) fibrin gels. Methods: Here we presented a genome-wide map of methylated cytosines for time-series samples in TRCs selection in 3D culture by whole-genome bisulfite sequencing (WGBS). Results: Comparative analysis revealed that the methylation degrees of many differentially methylated genes (DMGs) were increased by mechanical environment changed from 2D rigid to 3D soft. DMGs were significantly enriched in stemness related terms. TRCs in 1day had the highest non-CG methylation rate indicating its strong stemness. We found that genes with continuously increasing or decreasing methylation like CREB5/ADAMTS6/LMX1A may also affect the TRCs screening process. Furthermore, results showed that stage-specific/common CSCs markers were biased toward changing their methylation in non-CG (CHG and CHH, where H corresponds to A, T or C) methylation and enriched in gene body region. Conclusions: WGBS provides DNA methylome in the TRCs screening. The degree alteration of non-CG methylation was greater than CG (or CpG) and most of non-CG methylated genes were involved in cancer and mechanical transduction. The non-CG methylation may play an important role in the TRCs screening process. It was confirmed that non-CG DNA methylation plays an important role in the TRCs selection, which indicating that it is more sensitive to mechanical microenvironment and affects TRCs by regulating the expression of stemness genes in tumor cells.